Mapping genes controlling percentage and rate of germination in sunflower under salinity stress conditions - F. Morsali Aghajari; R. Darvishzadeh; H. Hatami Maleki (علوم و فناوری بذر ایران)
Salt stress is one of the most serious limiting factors for crop growth and production. In order to study the effect of salinity stress on the percentage and rate of germination of sunflower seeds and localization of genes controlling the traits in sunflower genome, a factorial experiment in a completely randomized design with three replications were conducted in Department of Plant Breeding and Biotechnology, Urmia University. The first factor was 70 recombinant inbred lines (RILs) of sunflower derived from the cross PAC2 (female parent) × RHA266 (male parent) together with parents and the second factor was salinity stress levels including 0, 2, 4, 6 and 8 dS/m. The results of analysis of variance revealed statistically significant differences among RILs and salinity levels based on two studied traits in 1% probability level and also significant interaction of Line by Salt stress. Heritability for germination rate and percentage was estimated 20% and 14%, respectively. Mapping of genes was performed using constructed SSR/SNP linkage map including 221 markers with average distance of 7.44 CM between markers. In several salinity levels, 22 QTLs for germination rate and 12 QTLs for germination percentage were detected. The effects of detected QTLs were varied between 2.04% to 67.61%. In this study, QTLs including salt2.PGS.13.1, salt2.PGS.2.1, salt2.GR.1.1, salt4.GR.9.1, salt6.GR.10.1 and salt8.GR.6.1 exhibited maximum phenotypic coefficient of variation. The results of this study revealed some non-specific QTLs (co-localized) for studied charactristics which are valuable in plant breeding programs and make it possible to have simultaneous selection for several charactristics.